Large intramuscular plexiform neurofibroma of thigh: a multidisciplinary team approach - Mandal, Aminda; Kumar, Satyam; Sinha, Avinash K.; Kumar, Deepak; Dwivedi, Prabhat K.; Panchbhai, Nikesh D.; Pandey, Lavleen (International Journal of Research in Orthopaedics, 2020)
Large plexiform neurofibroma of lower extremity involving the muscle is a rare entity. In this article we present the case of plexiform neurofibroma of right thigh involving the muscular plane and entrapment of the sciatic nerve. A 28 year lady presented with a plexiform neurofibroma of right thigh of size 60 cm×30 cm×25 cm with a positive family history of neurofibromatosis type 1. MRI was done for the assessment of the tumour and the adjacent structure involvement. The neurofibroma was removed with a multidisciplinary team approach with an intensive peri operative management. The pathological diagnosis was plexiform neurofibroma with diffuse neurofibroma. We have reported a rare case of large plexiform neurofibroma of lower extremity with muscle involvement and nerve entrapment.